İRAN MEŞRUTİYET HAREKETLERİNE RUSYA’NIN BAKIŞI VE MEŞRUTİYET KARŞITLARINA DESTEĞİ - Gökhan BOLAT (Fırat University, 2019)
Russia was one of the two states that dominated Iran in the beginning of the 20th. century. In 1907, the territory of Iran was